2012
DOI: 10.1016/j.neuron.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Specific Targeting of Direction-Selective Neurons in the Zebrafish Optic Tectum

Abstract: Direction selectivity (DS) is an important neuronal property in the visual system, but how DS is generated beyond the retina remains controversial. Here, we report a close correspondence between the preferred direction (PD) and the morphology of DS cells in the optic tectum. Ca(2+) imaging in cells expressing the genetically encoded Ca(2+) indicator GCaMP3 and multiphoton-targeted patch-clamp recordings allowed us to compare structure and function in single neurons. The arbors of differently tuned cell types s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 62 publications
(80 reference statements)
8
111
0
Order By: Relevance
“…This suggests a pre-calculated gradation in behavior based on the perceived distance of the prey item. There are certainly computational mechanisms that could accomplish this, such as the direction, orientation and size selectivity of tectal neurons (Del Bene et al, 2010;Gabriel et al, 2012;Grama and Engert, 2012;Niell and Smith, 2005;. How these mechanisms help calculate distance or direction of travel of paramecia is unknown.…”
Section: Circuit Mechanisms Governing Capturementioning
confidence: 99%
“…This suggests a pre-calculated gradation in behavior based on the perceived distance of the prey item. There are certainly computational mechanisms that could accomplish this, such as the direction, orientation and size selectivity of tectal neurons (Del Bene et al, 2010;Gabriel et al, 2012;Grama and Engert, 2012;Niell and Smith, 2005;. How these mechanisms help calculate distance or direction of travel of paramecia is unknown.…”
Section: Circuit Mechanisms Governing Capturementioning
confidence: 99%
“…Similarly, in zebrafish, it has been shown that the spatial pattern of visual inputs is arranged in tectal space according to the direction selectivity of the individual axons (Gabriel et al 2012). The mechanism(s) underlying how different sets of inputs are consistently guided to specific regions of the dendrite, however, is (are) not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiological studies have revealed that direction selective neurons widely exist in different animal species, including invertebrates and vertebrates, such as fly, beetle, locust, zebrafish, cat, rabbit [29], [46]- [55]. There are many ways to construct a directional selective neural network (DSNN) model [29], [31], [56].…”
Section: Research Links Directional To Rotational Selective Neuronsmentioning
confidence: 99%